Upaya Peningkatan Motivasi Siswa Dengan Metode Penilaian Portofolio Pada Pelajaran Pkwu Di Kelas Xi Iis 5 - Burwati Annisah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This portfolio assessment is a new approach that is often implemented in schools, especially for the assessment of students in the classroom. Portfolio is defined as a collection of learning outcomes or the work of students at the time in a subject. Crafts and entrepreneurship are one of the compulsory subjects of group B which contain a lot of skills with an assessment in the form of a portfolio. It aims to support and complement the National Curriculum. So that the learning and teaching process at SMA Negeri 16 Padang, especially class XI IIS 5 can run effectively and creatively, one of the learning methods that can be done is learning with portfolio assessments that can make students more motivated and innovative. The method with portfolio assessment is a learning strategy, where the teacher can know the development of students' knowledge and abilities in certain subjects. The results obtained from this classroom action research can be concluded that students' learning motivation has increased, the portfolio assessment method can increase students' learning motivation Portfolio assessment can apply learning that is relevant to the appreciation of a work